The Environmental Efficiency in RA Agrarian Sector: Dynamics and Prospects - Asatryan, Hovhannes Simon; Erkoyan, Arsen Slavik (ՀՀ ԳԱԱ ՏԻ)
In the conditions of current global developments (the ever-growing population of the Earth, the issue of poverty and food security, and global warming) the effective use of natural resources is gaining momentum and is imperative. The issue of environmental efficiency is manifested in the RA agrarian sector, also, considering the food security issues that our country faces, it is necessary to ensure the increase in food production through the effective use of natural resources and conditions. The main goal of the article is to study the dynamics of the environmental efficiency of the agrarian sector of Armenia, and within the framework of the article, the following tasks were set:  To study the methodological approaches to the assessment of the environmental efficiency of.  Based on the conducted research, assess the environmental efficiency of the agrarian sector for the past decade.  Perform the comparative analysis between the obtained results, distinguishing the observed trends and outlining the perspectives of environmental efficiency. Ներկայիս գլոբալ զարգացումների ֆոնին (մոլորակի անընդհատ աճող բնակչությունը, աղքատության հիմնախնդիրը, պարենապահովման հարցը, գլոբալ տաքացումը) առանձնահատուկ կարևորություն է ստանում արդյունավետ բնօգտագործումը։ Այս հիմնախնդիրը վառ արտահայտված է ՀՀ տնտեսության ագրարային ոլորտում, հետևաբար հաշվի առնելով մեր երկրի առջև ծառացած պարենապահովման հիմնահարցերը, պետք է ապահովել պարենի արտադրության ավելացումը՝ արդյունավետ բնօգտագործման ճանապարհով։ Հոդվածի հիմնական նպատակն է ուսումնասիրել բնօգտագործման արդյունավետության դինամիկան ՀՀ ագրարային ոլորտում, և այդ շրջանակներում առաջադրվել են հետևյալ հիմնական խնդիրները․  Ուսումնասիրել բնօգտագործման արդյունավետության գնահատման մեթո-դաբանական մոտեցումները,124  Կատարված ուսումնասիրության հիման վրա իրականացնել ՀՀ ագրարային ոլորտում բնօգտագործման արդյունավետության գնահատում՝ առանձին տարիների կտրվածքով,  Կատարել համեմատական վերլուծություն ստացված արդյունքների միջև՝ առանձնացնելով նկատվող տենդենցները և նախանշել բնօգտագործման հեռանկարները։
Keywords: Environmental economics